Implementasi Metode Talaqqi dalam Menghafal Surah Pendek pada Anak Usia Dini di RA Al- Junaidiyah Kampung Lama - Rizkiyah Nur Lubis; Sartika Dewi Harahap; Ali Masran Daulay (Ta'rim: Jurnal Pendidikan dan Anak Usia Dini, 2025)
This research aims to determine the implementation of the Talaqqi method in memorizing short surahs in early childhood at RA Al-junaidiyah Kampung Lama. This research uses a descriptive qualitative research method (field research), which includes data collection carried out by direct observation. The results of this research are (1) Implementation of the Talaqqi method in memorizing short surahs in early childhood. Where teachers at RA Al-junaidiyah have implemented the Talaqqi method well (2) Children's ability to memorize short surahs in early childhood. The ability of children to memorize short surahs in RA Al-junaidiyah varies, with some children being fast at memorizing, some being moderate and some being slow. The subjects for memorizing this short surah were 23 students from the rose class. There are 8 children who are developing very well, 14 children are developing according to expectations, while 2 children are starting to develop. (3) The supporting factors in implementing the Talaqqi method are health factors, intelligence factors and motivation factors. Meanwhile, the inhibiting factors in implementing the Talaqqi method are the child's lack of patience, the child's lack of seriousness and the child's lack of focus in memorizing.